2018
DOI: 10.1016/j.msea.2017.10.091
|View full text |Cite
|
Sign up to set email alerts
|

High temperature creep properties of a linear friction welded newly developed wrought Ni-based superalloy

Abstract: AD730 TM Ni-based superalloy specimens in solution-treated conditions were linear friction welded. Then, post-weld heat treatment (PWHT), consisting of γ´ sub-solvus solution treatments followed by aging, was conducted on the linear friction welded samples. High temperature creep tests were performed on the as-welded and PWHTed joints at two different temperatures: 700°C under 600 and 750 MPa stress levels, and 850°C under 100 and 200 MPa stresses. The creep resistance of the PWHTed joints was higher than that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…7(a-d), a large number of dimple like features that are visible at the fracture surface. Such surface characteristics have already been also reported in other superalloys [35,40,41]. They have been related to the growth (Fig 7 a and b) and coalescence of voids (Fig.…”
Section: Fracture Surface Analysissupporting
confidence: 81%
See 2 more Smart Citations
“…7(a-d), a large number of dimple like features that are visible at the fracture surface. Such surface characteristics have already been also reported in other superalloys [35,40,41]. They have been related to the growth (Fig 7 a and b) and coalescence of voids (Fig.…”
Section: Fracture Surface Analysissupporting
confidence: 81%
“…Specifically, the authors reported that the occurrence of liquation in the vicinity and within grain boundaries degraded the ductility of the alloy under tension and, as such, the alloy failed without plastic deformation [50]. Furthermore, as reported by other investigators [34,37,40], complete dissolution of γ' particles in the matrix of AD730 TM occurred at 1200ºC which resulted in significant weakening of the grain boundaries in which liquation could occur. In general, intergranular cracking at high temperatures takes place at locations with localized stress or structural imperfections such as the grain boundary edges, triple points, and interface of brittle particles and are accompanied with grain boundary slipping and the formation voids [36,51,52].…”
Section: Analysis Of the Flow Curvesmentioning
confidence: 75%
See 1 more Smart Citation
“…IN718 is a high strength superalloy extensively used for blade applications in gas turbines due to its good weldability and excellent resistance to cracking [20][21][22]. AD730 TM is a Ni-based alloy recently developed by Auber & Duval Company as a new forged Ni-based superalloy for turbine disk applications, and its mechanical properties are comparable to those of other Ni-based superalloys such as Waspaloy, Udimet720 and IN718Plus [13,14,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…1921 There is a high demand in using computational methods to predict the material thermal processes and material deformation. 2224 So far, there has been extensive research on LFW, in relation to studies on the welding processes, 2529 microstructural characterization, 3033 numerical simulation, 11,3439 and analytical computation. 35,4043
Figure 1.Linear friction welded integrally bladed-disk (blisk) manufactured at TWI.
…”
Section: Introductionmentioning
confidence: 99%